The Capital Structure Theory and its Practical Implications for Firm Financial Management in Central and Eastern Europe - Marian Rizov (EMERGO Journal of Transforming Economies and Societies, 2001)
The paper reviews and interprets capital structure theory in a stylized way and explains the conceptual issues, consequences, and implications for financial management. Firms face an uncertain world that does not co-operate with many of the assumptions of the theory. Specific attention is paid to the important issues concerning the capital structure of firms in transition economies. By reconciling empirical evidence with theory practical strategies for managing capital structure in transition are suggested. Thus the higher the risk and volatility in the economy, the lower the proportion of debt in the capital structure should be. Reserving some unused good debt capacity is useful to provide flexibility and lead to increase in firm value.
Keywords: G30; P20; 330; capital structure; transition economies; financial management; soft budget constraint